(untitled) (Materiali di Estetica. Terza serie, 2024)
A dying SS repentant of a horrible crime begs for forgiveness from a Jewish prisoner in concentration camp. He listens in silence, then asks fellow Jews and a seminarian. He will ask the same question to 47 intellectuals arousing a debate in which they confront each other human pity and justice towards those absent (the murdered Jews people). The present time cannot resolve the question on the forgiveness question, which just history and transcendence may answer.